Strength assessment of mining soil treated with steel slag as liner material for retention pond - Noratiqah Masri (2022)
Clay soil has always been associated with low shear strength and high compression behavior due to the high content of organic matter. The limited amounts of clay available onsite and acid mine drainage (AMD) problems have necessitated the continuous search for the treatment technology potentials. Mining soils, obtained from Selinsing Gold Mine in Raub, Pahang were evaluated to determine their suitability for use as mining soil and steel slag mixtures as compacted retention pond liners for AMD treatment. The studied samples were subjected to classification, compaction, permeability and strength tests. The results indicated that the index properties of the samples met the minimum requirements for use as liners. The compaction test showed that the maximum dry density (MDD) and optimum moisture content (OMC) decreased and increased, respectively, for all studied samples. At OMC, hydraulic conductivities of the compacted soil-steel slag were in the order of ≤ 10-⁹ m/s. The results from unconfined compression strength (UCS) tests gave values of 204 kN/m² and 61º for soil cohesion and soil internal friction angle, respectively. Furthermore, the influence of steel slag treatment on strength properties has generally shown an improvement of up to 15% steel slag which gives the acceptable results of stress-strain in respect of its usability as liner material.